Raman-Based Diagnostics of Biotic and Abiotic Stresses in Plants. A Review - Payne, William Z.; Kurouski, Dmitry (Frontiers in Plant Science, 2021)
Our civilization is facing one of the biggest challenges that it has never experienced before: we must increase food production on 70% of to feed 9.7 billion people by 2050. These food demands can be met only by development of innovative agricultural technologies. This novel agricultural philosophy, also known as digital farming, aims to maximize crop yield with minimal environmental impact. Raman spectroscopy (RS) is an emerging analytical technique that can be used for non-invasive, non-destructive and confirmatory diagnostics of diseases, as well as nutrient deficiencies in plants. It is also capable of probing nutrient content of seeds. Recent findings show that Raman can be used for non-invasive phenotyping and digital selection of plants. These pieces of evidence suggest that RS can be used for chemical-free surveillance of plant health directly in the field. High selectivity and specificity of this technique suggest that the use of RS will transform agriculture in the U.S. This review highlights the advantages of RS for detection of plant diseases, nutrient deficiencies, and phenotyping.